2008
DOI: 10.1123/apaq.25.3.189
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Quality of Life Experienced by Highly Active Individuals with Physical Disabilities

Abstract: The present study examined links between physical activity and quality of life experienced by individuals with physical disabilities recruited from a wheelchair user’s basketball tournament. The participants included 12 male and 14 female adults between the ages of 18–54 (M = 31.12, SD = 10.75) who all reported one or more condition(s) that impacted their daily living. They were administered the Physical Activity Scale for Individuals with Physical Disabilities (Washburn, Weimo, McAuley, Frogley, & Figoni,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
14

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 0 publications
4
59
0
14
Order By: Relevance
“…4 The PASIPD seems to discriminate between groups of people with different disabilities. The average total PASIPD score (17.8 MET h day À1 ) was comparable to that of other studies that included mostly persons with SCI or elderly with chronic conditions (PASIPD scores varied between 11.0 and 36.3 MET h day À1 ) 4,[11][12][13][14][15][16] (Figure 2). This study used 11 items in contrast to the other studies (12 items).…”
Section: Discussionsupporting
confidence: 81%
“…4 The PASIPD seems to discriminate between groups of people with different disabilities. The average total PASIPD score (17.8 MET h day À1 ) was comparable to that of other studies that included mostly persons with SCI or elderly with chronic conditions (PASIPD scores varied between 11.0 and 36.3 MET h day À1 ) 4,[11][12][13][14][15][16] (Figure 2). This study used 11 items in contrast to the other studies (12 items).…”
Section: Discussionsupporting
confidence: 81%
“…No entanto, o tempo gasto dos atletas com a prática das modalidades esportivas, bem como, com a prática do exercício físico também podem interferir em outros fatores da vida, como, a qualidade de vida (QV) 5 .…”
Section: Introductionunclassified
“…Studies exploring social interactions in disability sport are particularly relevant as previous research indicates that youth with disabilities may be at increased risk for peer rejection or neglect (Martin & Choi, 2009). Finally, since it has been suggested that sport may provide an effective avenue to combat the discrimination and stigma commonly experienced by individuals with disabilities (Giacobbi, Stancil, Hardin, & Bryant, 2008), research within this setting is warranted. Fortunately, there is growing support for the notion that sport can be a fertile developmental context for youth with disabilities (e.g., Kristén, Patriksson, & Fridlund, 2002;Martin, 2006).…”
Section: Introductionmentioning
confidence: 99%